Coupled effects of reflection and absorptive gas mixture on surface temperature determined by single color pyrometer. (May 2019) - Huang, Yunwei; Long, Mujun; Zhao, Jingjun; Fan, Helin; Chen, Dengfu; Tan, Kai; Duan, Huamei
Highlights: An analytical radiation thermometry model considering both reflected ambient radiation and absorption and emission of radiation by interfering gas is developed. The temperature errors caused by interfering gas and reflected ambient radiation are quantitatively analyzed. The selection methodologies of spectral pass-band of radiation thermometer to minimize the influences of reflection and gas mixture absorption and emission under different conditions are proposed. Abstract: To investigate the coupling effects of reflection and absorptive gas mixture on surface temperature determined by single color pyrometer, an analytical radiation thermometry model combined with a mathematical radiative heat transfer model, which simultaneously considering both the reflected ambient radiation and the gas absorption and emission of radiation, was established in this paper. The temperature errors caused by the combination of intervening gas mixture and reflected ambient radiation were quantitatively analyzed under three practicable measurement strategies depending on the relative target and gas temperatures. As the results indicate, the investigated wavelength ranges can be roughly divided into three parts depending on the relative importance of reflection and gas mixture. Correcting for the hot/cool gas mixture effect through use of a low/high temperature reflector is usually effective because these two effects will cancel each other out. The selection methodology of spectral pass-band of radiation thermometer to minimize the influences of reflection and gas mixture absorption and emission under different conditions was presented. Sensitivity analysis of the derived temperature error to the variations in ambient temperature, target surface emissivity, gas mixture temperature and concentration, and viewing path length was investigated. Considering the case T 1 = 1200 K, T 2 = 1400 K, Tg = 2000 K, ε 1 = 0.85, L = 100 cm, X H 2 O = 0.2, X C O 2 = 0.1, p = 1 atm, the most influential factor is gas mixture temperature for wavelength longer than 1.33 µm, followed by other factors. For wavelength shorter than 1.33 µm, the high ambient temperature is the main contributor to the imprecision in the proposed model output. The analyses in the paper may provide the necessary theoretical supports for the design and application of a radiation thermometer in the presence of intervening gas.